Relação entre área do braço, área do músculo, área de gordura do braço e a menarca em adolescentes do município de Botucatu - Goldberg, T. B. [UNESP]; Colli, A. S.; Curi, P. R. (Jornal De Pediatria, 1996)
The authors show the relations among arm circumference, arm muscle and arm fat areas with or without menarche, by carrying out an anthropometric study in 717 adolescents in the municipality of Botucatu. It must be emphasized that those adolescents who had already menstruated presented significantly higher nutritional indicators than those who had not menstruated yet. There was an increase in fat tissue and lean body mass in those adolescents who had already menstruated. Body changes might be expressed by calculating muscle and arm fat areas using triceps skinfold and arm circumference.
Relations among arm, arm muscle, arm fat areas and menarche in adolescents in the municipality of Botucatu